Abstracts DEGRO 2019 Niedrig dosierte Röntgenstrahlung beeinflusst die Makrophagenpolarisation im Zusammenspiel mit Synovialfibroblasten auf eine anti-entzündliche Art und Weise - Deloch, Lisa; Fuchs, Jana; Rückert, Michael; Frey, Benjamin; Gaipl, Udo (2019)
Created from Fastlane, Scopus look-up

Evaluation of adenoviral vector Ad19a encoding RSV-F as novel vaccine against respiratory syncytial virus - Fuchs, Jana; Hübner, Julian; Schmidt, Anna; Irrgang, Pascal; Maier, Clara; Vieira Antao, Ana Isabel; Oltmanns, Friederike; Thirion, Christian; Lapuente, Dennis; Tenbusch, Matthias (npj Vaccines, 2024)
Respiratory syncytial virus (RSV) is the leading cause of severe lower respiratory tract infections in infants and toddlers. Since natural infections do not induce persistent immunity, there is the need of vaccines providing long-term protection. Here, we evaluated a new adenoviral vector (rAd) vaccine based on the rare serotype rAd19a and compared the immunogenicity and efficacy to the highly immunogenic rAd5. Given as an intranasal boost in DNA primed mice, both vectors encoding the F protein provided efficient protection against a subsequent RSV infection. However, intramuscular immunization with rAd19a vectors provoked vaccine-enhanced disease after RSV infection compared to non-vaccinated animals. While mucosal IgA antibodies and tissue-resident memory T-cells in intranasally vaccinated mice rapidly control RSV replication, a strong anamnestic systemic T-cell response in absence of local immunity might be the reason for immune-mediated enhanced disease. Our study highlighted the potential benefits of developing effective mucosal against respiratory pathogens.
CRIS-Team Scopus Importer:2024-11-15

Low-Dose Irradiation Differentially Impacts Macrophage Phenotype in Dependence of Fibroblast-Like Synoviocytes and Radiation Dose - Fuchs, Jana; Rueckert, Michael; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Deloch, Lisa (Journal of Immunology Research, 2019)
Rheumatoid arthritis (RA) is a multifactorial autoimmune disease whose main hallmark is inflammation and destruction of the joints. Two cell types within the synovium that play an important role in RA are fibroblast-like synoviocytes (FLS) and macrophages. The latter innate immune cells show a high plasticity in their phenotype and are central in inflammatory processes. Low-dose radiotherapy (LD-RT) with particularly a single dose of 0.5 Gy has been demonstrated to have a positive impact on pain, inflammation, and bone in inflamed joints. We now examined for the first time how LD-RT influences FLS and bone marrow-derived macrophages in co-culture systems of an experimental model of RA to reveal further mechanisms of immune modulatory effects of low and intermediate dose of ionizing radiation. For this, the bone marrow of hTNF-alpha tg mice was differentiated either with cytokines to obtain key macrophage phenotypes (M0, M1, and M2) or with supernatants (SN) of untreated or irradiated FLS. Flow cytometry analyses were used to analyse the impact of radiation (0.1, 0.5, 1.0, and 2.0 Gy) on the phenotype of macrophages in the presence or absence of SN of FLS. LD-RT had no impact on cytokine-mediated macrophage polarization in M0, M1, or M2 macrophages. However, SN of irradiated FLS particularly reduced CD206 expression on macrophages. Macrophage phenotype was stable when being in contact with SN of nonirradiated FLS, but significantly increased surface expression of CD206 and slightly decreased CD80 and CD86 expression were observed when macrophage themselves were irradiated with 0.5 Gy under these microenvironmental conditions, again highlighting discontinuous dose dependencies in the low and intermediate dose range. One can conclude that FLS-dependent microenvironmental conditions have a slight influence on the modulation of macrophage phenotype under radiation exposure conditions. Future studies are needed to reveal the impact of radiation exposure on the functions of treated macrophages under such microenvironmental conditions.
CRIS-Team WoS Importer:2019-09-13

Low-Dose Radiotherapy Ameliorates Advanced Arthritis in hTNF-α tg Mice by Particularly Positively Impacting on Bone Metabolism - Deloch, Lisa; Derer, Anja; Hueber, Axel; Herrmann, Martin; Schett, Georg; Wölfelschneider, Jens; Hahn, Jonas; Rühle, Paul-Friedrich; Stillkrieg, Willy; Fuchs, Jana; Fietkau, Rainer; Frey, Benjamin; et al. (Frontiers in Immunology, 2018)
Inflammation and bone erosion are central in rheumatoid arthritis (RA). Even though effective medications for control and treatment of RA are available, remission is only seen in a subset of patients. Treatment with low-dose radiotherapy (LD-RT) which has been already successfully used for amelioration of symptoms in benign diseases should be a promising approach to reduce pain, inflammation, and particularly bone erosion in patients with RA. Even though anti-inflammatory effects of LD-RT are already described with non-linear dose response relationships, and pain-reducing effects have been clinically observed, the underlying mechanisms are widely unknown. Besides immune cells many other cell types, such as fibroblast-like synoviocytes (FLS), osteoclasts, and osteoblast are present in the affected joint and might be modulated by LD-RT. For this study, these cell types were obtained from human tumor necrosis factor-α transgenic (hTNF-α tg) mice and were consecutively exposed to different doses of ionizing radiation (0.1, 0.5, 1.0, and 2.0 Gy, respectively) in vitro. In order to study the in vivo effects of LD-RT within the arthritic joint, hind paws of arthritic hTNF-α tg mice were locally irradiated with 0.5 Gy, a single dose per fraction that is known for good clinical responses. Starting at a dose of 0.5 Gy, proliferation of FLS was reduced and apoptosis significantly enhanced with no changes in necrosis. Further, expression of RANK-L was slightly reduced following irradiation with particularly 0.5 Gy. Starting from 0.5 Gy, the numbers of differentiated osteoclasts were significantly reduced, and a lower bone resorbing activity of treated osteoclasts was also observed, as monitored via pit formation and Cross Laps presence. LD-RT had further a positive effect on osteoblast-induced mineralization in a discontinuous dose response relationship with 0.5 Gy being most efficient. An increase of the gene expression ratio of OPG/RANK-L at 0.1 and 0.5 Gy and of production of OPG at 0.5 and 1.0 Gy was observed. In vivo, LD-RT resulted in less severe arthritis in arthritic hTNF-α tg mice and in significant reduction of inflammatory and erosive area with reduced osteoclasts and neutrophils. Locally applied LD-RT can, therefore, induce a beneficial micro-environment within arthritic joints by predominantly positively impacting on bone metabolism.
EVALuna2:34663
Keywords: rheumatoid arthritis; inflammation; low-dose radiotherapy; bone metabolism; synovial-like fibroblasts; osteoclasts; osteoblasts

Mucosal immunization with an adenoviral vector vaccine confers superior protection against RSV compared to natural immunity - Maier, Clara; Fuchs, Jana; Irrgang, Pascal; Wissing, Michael Hermann; Beyerlein, Jasmin; Tenbusch, Matthias; Lapuente, Dennis (Frontiers in Immunology, 2022)
Respiratory syncytial virus (RSV) infections are the leading cause of severe respiratory illness in early infancy. Although the majority of children and adults mount immune responses against RSV, recurrent infections are frequent throughout life. Humoral and cellular responses contribute to an effective immunity but also their localization at respiratory mucosae is increasingly recognized as an important factor. In the present study, we evaluate a mucosal vaccine based on an adenoviral vector encoding for the RSV fusion protein (Ad-F), and we investigate two genetic adjuvant candidates that encode for Interleukin (IL)-1β and IFN-β promoter stimulator I (IPS-1), respectively. While vaccination with Ad-F alone was immunogenic, the inclusion of Ad-IL-1β increased F-specific mucosal immunoglobulin A (IgA) and tissue-resident memory T cells (TRM). Consequently, immunization with Ad-F led to some control of virus replication upon RSV infection, but Ad-F+Ad-IL-1β was the most effective vaccine strategy in limiting viral load and weight loss. Subsequently, we compared the Ad-F+Ad-IL-1β-induced immunity with that provoked by a primary RSV infection. Systemic F-specific antibody responses were higher in immunized than in previously infected mice. However, the primary infection provoked glycoprotein G-specific antibodies as well eventually leading to similar neutralization titers in both groups. In contrast, mucosal antibody levels were low after infection, whereas mucosal immunization raised robust F-specific responses including IgA. Similarly, vaccination generated F-specific TRM more efficiently compared to a primary RSV infection. Although the primary infection resulted in matrix protein 2 (M2)-specific T cells as well, they did not reach levels of F-specific immunity in the vaccinated group. Moreover, the infection-induced T cell response was less biased towards TRM compared to vaccine-induced immunity. Finally, our vaccine candidate provided superior protection against RSV infection compared to a primary infection as indicated by reduced weight loss, virus replication, and tissue damage. In conclusion, our mucosal vaccine candidate Ad-F+Ad-IL-1β elicits stronger mucosal immune responses and a more effective protection against RSV infection than natural immunity generated by a previous infection. Harnessing mucosal immune responses by next-generation vaccines is therefore a promising option to establish effective RSV immunity and thereby tackle a major cause of infant hospitalization.
CRIS-Team Scopus Importer:2022-09-09
Keywords: adenoviral (Ad) vector; IgA; mucosal; natural immunity; RSV (respiratory syncytial virus); tissue-resident memory T cells; TRM; vaccine

Protective mucosal immunity against SARS-CoV-2 after heterologous systemic prime-mucosal boost immunization - Lapuente, Dennis; Fuchs, Jana; Willar, Jonas; Vieira Antao, Ana Isabel; Eberlein, Valentina; Uhlig, Nadja; Issmail, Leila; Schmidt, Anna; Oltmanns, Friederike; Peter, Antonia Sophia; Müller-Schmucker, Sandra; Irrgang, Pascal; et al. (Nature Communications, 2021)
Several effective SARS-CoV-2 vaccines are currently in use, but effective boosters are needed to maintain or increase immunity due to waning responses and the emergence of novel variants. Here we report that intranasal vaccinations with adenovirus 5 and 19a vectored vaccines following a systemic plasmid DNA or mRNA priming result in systemic and mucosal immunity in mice. In contrast to two intramuscular applications of an mRNA vaccine, intranasal boosts with adenoviral vectors induce high levels of mucosal IgA and lung-resident memory T cells (TRM); mucosal neutralization of virus variants of concern is also enhanced. The mRNA prime provokes a comprehensive T cell response consisting of circulating and lung TRM after the boost, while the plasmid DNA prime induces mostly mucosal T cells. Concomitantly, the intranasal boost strategies lead to complete protection against a SARS-CoV-2 infection in mice. Our data thus suggest that mucosal booster immunizations after mRNA priming is a promising approach to establish mucosal immunity in addition to systemic responses.
CRIS-Team Scopus Importer:2021-12-10